2022
DOI: 10.3390/drones6040081
|View full text |Cite
|
Sign up to set email alerts
|

Deriving First Floor Elevations within Residential Communities Located in Galveston Using UAS Based Data

Abstract: Flood damages occur when just one inch of water enters a residential household and models of flood damage estimation are sensitive to first-floor elevation (FFE). The current sources for FFEs consist of costly survey-based elevation certificates (ECs) or assumptions based on year built, foundation type, and flood zone. We sought to address these limitations by establishing the role of an Unmanned Aerial System (UAS) to efficiently derive accurate FFEs. Four residential communities within Galveston Island, Texa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These neighborhoods have FEMA’s E.C. data and reliable FFE estimates (Diaz et al, 2022) for validation. The samples showed that our workflow is well applicable to Galveston, so we applied the method to all buildings recorded in Galveston Island’s building footprint data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These neighborhoods have FEMA’s E.C. data and reliable FFE estimates (Diaz et al, 2022) for validation. The samples showed that our workflow is well applicable to Galveston, so we applied the method to all buildings recorded in Galveston Island’s building footprint data.…”
Section: Resultsmentioning
confidence: 99%
“…Different from traditional field surveys that rely on manual measurements, our measurement from SVI based on computer vision technology is capable of processing enormous amounts of data. Contributing to the generalizability of our research, the initial data for the proposed workflow can be derived either from the building footprints or a single list of addresses of the target area; for instance, the dataset Galveston_FFEData2020 (Diaz et al, 2022), which is used for accuracy validation in this research, identifies unique houses using only street addresses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinates are the basis to download the street view images (SVIs) from Google Maps as well as the depth maps corresponding with each SVI. Considering the generalizability of our research, the initial data of the proposed workflow can either start from the building footprints or a single list of addresses of the target area (Diaz et al, 2022). For instance, the dataset of Galveston used for accuracy validation only contains addresses but not the coordinate position as the major label for data.…”
Section: Data Collectionmentioning
confidence: 99%
“…Also, the developed RF model was based on the information derived from EC that is unavailable for most flood‐prone areas worldwide, and its preparation is time‐consuming and a tedious task. Diaz et al (2022) used a positioning‐enabled unmanned aerial system (UAS) and created a detailed 3D photogrammetric model to estimate the FFE of the buildings in Galveston Island, Texas. Although the reported mean absolute error was promising (0.16 m), the method is costly and does not apply to large areas.…”
Section: Introductionmentioning
confidence: 99%